Strategic Management Approaches of Schools under the Secondary Education Service Area Office 39 - Yaengjun, Nuttapong; Chaowachai, Sathiraporn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The purposes of this research were to study the need assessment and the strategic management approaches of schools under the Secondary Educational Service Area 39. Data were collected from the sample of 114 administrators and teachers responsible for school plans under the Secondary Educational Service Area 39. The research instrument was a questionnaire used for collecting data about current and desirable conditions of strategic management of schools under the Secondary Educational Service Area Office 39. Data collected were then analyzed to determine Modified Priority Needs Index (PNImodified). The results were then used to develop the interview questions used for collecting data about strategic management of schools under the Secondary Educational Service Area Office 39. The interview were conducted with five administrators and teachers responsible for school plans. Data collected were then analyzed for further presentation. The results of this research could be indicated as follow: 1) The Modified Priority Needs Index (PNImodified) of overall needs for strategic management of schools under the Secondary Educational Service Area Office 39 was 0.209. The highest Modified Priority Needs Index was on environmental analysis (PNImodified = 0.251), while the lowest Modified Priority Needs Index was on strategy implementation (PNImodified = 0.145) 2) There were 16 approaches of strategic management of schools under the Secondary Educational Service Area Office 39.